Feed palatability test on Hornbill in Taman Rusa - Nanda Yustina; Abdullah Abdullah; Devi Syafrianti (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2017)
Feed palatability level of animals is very important, as this will affect the growth and development of animals, and also for  the success of captivity animal itself. The aim of this study is to determine feed palatability level on hornbill in Taman Rusa. This study used descriptive method. Analysis of the data calculated using the feed palatability index selection. The results showed that the level of palatability of feed on each hornbill shows the level of palatability different. Palatability of feed on tomato hornbill 1 is a selection index with a value of 0.94, hornbill 2 papaya with a selection index value of 0.93, hornbill 3 tomatoes with Unmatched value with an index of 0.97, and a hornbill 4 tomatoes with value selection index 0.92. The conclusions of this study indicate three favorite feed hornbill showed the highest feed on tomatoes, and a hornbill shows favorite feed is papaya. Based on the research that has been done, then feeding for each hornbill better differentiated quantity between one another